Do natural resource sectors rely less on external finance than manufacturing sectors? - Christian Hattendorff (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
The finding that industrial sectors differ in their dependence on external finance for sector-specific technological reasons and, thus, rely to a different degree on financial development has become a major concept in studies conducted on both growth and trade. Although natural resources might play an important role in each of these fields, research on industries' financial dependence has been limited so far to manufacturing. By focusing on the natural resource sectors, the present paper aims to close this gap in its analysis. It rejects the common view that the natural resource industry in particular is less dependent on the financial system, and finds that the results of the analysis depend on the specific measure being applied. Measures relating investment and cash flow indicate high external dependence, while measures accounting for more short-term liquidity needs demonstrate rather low external dependence of natural resource firms. These results do not change considerably over time or across countries.
Keywords: G20; G30; O13; O14; O16; 330; Financial development; external dependence; natural resources